STUDY OF VALUES IN PEDAGOGICAL LITERATURE AS COMPONENT COMPETENCE OF A FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2008)
The article deals with some problems of value orientations in students’ life.